X-ray radiographic analysis of the two wooden sculptures of 18th century - Soraia Azeredo; Renan Oliveira; Elaine Gusmão; Marcelino Anjos; Francis Sanches; Ricardo Lopes; Davi Oliveira (Brazilian Journal of Radiation Sciences)
The X-ray radiography technique is highly efficient in investigating the manufacturing techniques employed by an artisan when creating a sculpture, as well as assessing the state of conservation and restoration processes. For instance, it allows the determination of whether the artist carved the sculpture from a single piece of massive wood or if it was sculpted in multiple parts, subsequently assembled using nails, hooks, or metal spikes. It also provides insights into whether the artwork underwent certain restoration processes and reveals its current state of preservation or degradation. This information can offer insights into the artist preferred creation technique, potentially the most popular technique of the time. It can also help estimate the period when the artwork underwent restoration and aid in choosing the appropriate restoration technique. In this study, we present the results of an investigative analysis of the internal structure, using digital X-ray radiography, of two wooden sacred sculptures representing biblical characters King David and his wife Bathsheba, dating back to the 18th century and housed in the Church of Our Lady of Pilar in Duque de Caxias, RJ, Brazil. Both sculptures are covered with layers of stain, with a prevailing golden hue on the garments. The obtained radiographic images show that the artist carved various parts of the sculptures and later assembled them using metal pegs. Additionally, recent nails were visible, indicating that the sculptures underwent a restoration process. All digital radiographic images were captured in high resolution using a flat-panel detector.